2020
DOI: 10.36959/624/439
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Coffee Husk Compost and Lime Amendment on Acidic Soil of Haru, Western Ethiopia

Abstract: A pot experiment was conducted to assess the effects of coffee husk compost, lime and their combinations on chemical properties of acidic soil and coffee seedling growth at Haru Research Sub-Center nursery site in west Wollega zone in 2016/17. Soil and coffee husk compost samples were collected, prepared and analyzed before and at the end of experiment following the standard laboratory procedures. The experiment was laid out in a factorial experiment arranged in Randomized Complete Block Design with three repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…e result of this study was also in line with several research findings [39][40][41][42][43][44][45][46][47], which conveyed that the application of organic fertilizer, particularly vermicompost, improved plant heights. Similar findings were also explored by Maru et al [48]; Sikder and Joardar [49]; and Bhattarai et al [50], who determined that the application of organic fertilizer in biochar form increased plant height in pea and rice crops.…”
Section: Plant Height (Cm)supporting
confidence: 90%
“…e result of this study was also in line with several research findings [39][40][41][42][43][44][45][46][47], which conveyed that the application of organic fertilizer, particularly vermicompost, improved plant heights. Similar findings were also explored by Maru et al [48]; Sikder and Joardar [49]; and Bhattarai et al [50], who determined that the application of organic fertilizer in biochar form increased plant height in pea and rice crops.…”
Section: Plant Height (Cm)supporting
confidence: 90%
“…According to Nduka et al (2015), coffee husk improved physico-chemical properties of soil, the nutrient in the nursery soil medium and actively supported the morphological development of the cashew seedling. Similar work by Bikila (2020) and Bikila et al (2020) confirmed that, amending acid soil with coffee husk/ pulp compost improved the soil physicochemical and biological properties that enhanced the coffee seedling growth in western Ethiopia, indicating the potential use of composted coffee husk/ pulp on the field as an alternative source of soil amendment to improve the nutrient content and ameliorate soil acidity problem in Ethiopia. Since good morphological development of seedling enhances their better field establishment, the use of coffee husk to amend nursery soil is recommended.…”
Section: Effect Of Coffee Husk and Pulp Compost On Crop Growthmentioning
confidence: 55%
“…The average temperature ranges are 11.60°C and 26.30°C, respectively. Chromic nitosols, cambisols, and fluvisols are the dominant soil types in the center [22].…”
Section: Description Of the Study Areasmentioning
confidence: 99%